2014
DOI: 10.1136/bmjopen-2014-005241
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported eating rate and metabolic syndrome in Japanese people: cross-sectional study

Abstract: ObjectivesTo examine the association between self-reported eating rate and metabolic syndrome.DesignCross-sectional study.SettingAnnual health checkup at a health check service centre in Japan.ParticipantsA total of 56 865 participants (41 820 male and 15 045 female) who attended a health checkup in 2011 and reported no history of coronary heart disease or stroke.Main outcome measureMetabolic syndrome was defined by the joint of interim statement of the International Diabetes Federation and the American Heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
99
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 39 publications
16
99
0
1
Order By: Relevance
“…The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters. This is consistent with the findings of many previous studies of the relationships between the objectively and subjectively assessed eating speeds and the body composition and shape (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Previous studies have also demonstrated that fast eating induces overeating, and that overeating is related to weight gain due to the ingestion of a larger volume of food before experiencing satiety (22)(23)(24).…”
supporting
confidence: 80%
See 3 more Smart Citations
“…The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters. This is consistent with the findings of many previous studies of the relationships between the objectively and subjectively assessed eating speeds and the body composition and shape (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Previous studies have also demonstrated that fast eating induces overeating, and that overeating is related to weight gain due to the ingestion of a larger volume of food before experiencing satiety (22)(23)(24).…”
supporting
confidence: 80%
“…Cross-sectional, longitudinal and experimental studies have provided strong evidence for fast eating inducing overweight (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The subjects in the present study who assessed themselves as fast eaters tended to be overweight and obese, and indeed ate the test meal with a smaller total number of chews and shorter total meal duration than did the slow eaters.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…The accumulation of healthy lifestyle behaviors has been shown to be associated with the prevention of CVD, stroke, metabolic syndrome, type 2 diabetes, hypertension and dyslipidemia [15][16][17][18][19]. The clarification of the association between the adherence to healthy lifestyle behaviors and the incidence of CKD may help to demonstrate the importance of lifestyle modification in CKD prevention.…”
Section: Introductionmentioning
confidence: 99%